How Can the Digital Agricultural Database be used for Policy Making? - Abay, Kibrom A. (2021)
The online start-up workshop presented the "Building a COVID-19 Rapid Response and Ag-Foresight Department in Egypt" project’s activities and future plans, including collaborative discussion and brainstorming with stakeholders on the most relevant issues and policies in the agricultural sector’s resilience during COVID-19.